2003
DOI: 10.1046/j.1365-2222.2003.01792.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of soluble CD30 in cord blood and peripheral blood during childhood are not correlated with the development of atopic disease or a family history of atopy

Abstract: These findings indicate that the sCD30 concentration in cord blood is not a reliable prognostic indicator of, nor a useful diagnostic marker for, atopic disease in children up to 7 years of age. If such correlations do exist, they might be masked by age-dependent variations in the circulating levels of sCD30, which may reflect individual differences in the maturation of children's immunological responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Moreover, contradictory data questioned the evidence for a role of CD30 in allergies. 9 By using CD30 2/2 mice and mAbs directed against CD30 receptor or ligand, we could clearly demonstrate in our well-established murine model of asthma that absence of CD30 signaling or blocking of CD30 signaling significantly reduces eosinophilic pulmonary inflammation. Moreover, CD30 signaling was critical for T H 2 cytokine production, as well as IgE production, in the murine asthma model because absence of CD30 expression or blocking of CD30 signaling significantly inhibited these parameters in OVA-immunized mice.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, contradictory data questioned the evidence for a role of CD30 in allergies. 9 By using CD30 2/2 mice and mAbs directed against CD30 receptor or ligand, we could clearly demonstrate in our well-established murine model of asthma that absence of CD30 signaling or blocking of CD30 signaling significantly reduces eosinophilic pulmonary inflammation. Moreover, CD30 signaling was critical for T H 2 cytokine production, as well as IgE production, in the murine asthma model because absence of CD30 expression or blocking of CD30 signaling significantly inhibited these parameters in OVA-immunized mice.…”
Section: Discussionmentioning
confidence: 75%
“…However, these data are all indirect, and moreover, contradictory data exist that do not support a role of CD30 in allergic diseases. 9 The aim of this study was to examine directly the role of the CD30/CD153 pathway in a murine model of allergic asthma. For this purpose, we examined mice deficient in CD30 and compared them with wild-type (WT) animals.…”
mentioning
confidence: 99%
“…CD30 is known as an activation marker belonging to the TNFR superfamily (13) that may be involved in a sequence of costimulatory mechanisms. Thus, the binding of CD30 to the CD30 ligand (CD30/CD153) is believed to be important in several immunoregulatory processes (14) and the expression of this receptor is depending on cell type and nature of microenvironment (15). One of the explanations that MFI of CD30 + CD4 + was lower in positive atopy history may be that the allergen stimulation at pregnancy in newborns with positive atopy family history was able to satiate T cells and the dose of mitogen required to stimulate cells in in vitro studies must have been higher than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Instead we evaluated the use of sCD30 in cord blood and in peripheral blood during childhood as a predictive marker for atopic disease and/or eczema in pediatric patients. We concluded that sCD30 was an unreliable marker for atopic disease and/or eczema in children (5).…”
mentioning
confidence: 93%
“…14 in Stencel‐Gabriel et al.) is further used to back‐up their statement ‘Thus, the binding of CD30 to the CD30ligand (CD30/CD153) is believed to be important in several immunoregulatory processes (14).’ It should be stressed that in this work (5), we did not at all investigate CD30–CD30L interactions or their possible immunoregulatory role. Instead we evaluated the use of sCD30 in cord blood and in peripheral blood during childhood as a predictive marker for atopic disease and/or eczema in pediatric patients.…”
mentioning
confidence: 94%